MEMAKSIMALKAN PERKEMBANGAN MOTORIK SISWA SEKOLAH DASAR MELALUI PELAJARAN PENJASKES - Oktafiana Kiranida (Program Studi Pendidikan Guru Sekolah Dasar, 2019)
Every child starting from the new born had started to move, in the scientific movement which carried out by the human body called the motor function. The process of growing a flower child in harmony with the maturity of the nerves and muscles of the child, so that the slightest movement made by a child is the result of the interaction of the various parts of the system in the body that is controlled by the brain, development the motor is a physical movement through the control activities the Center nerve, nerves and muscles are coordinated. Physical development of primary school age children in the form of coordination of body movements such as running, jumping, depending on tip toes, throw, and catch, as well as maintaining a balance. These activities are necessary in improving the coordination of movement motor skills. But at this age motor development becomes much smoother and more regular compared to infancy. they look faster running and good at jumping as well as able to maintain balance in the body. For smooth motor skills, children must continue to make physical activity and besides that the children should also be involved in the activities of the sports games gymnastics, swimming, etc. To the Lesson physical education and health subjects were very effective in maximizing the development of school-age students on motor base. Abstrak Setiap anak mulai dari baru lahir sudah mulai bergerak, didalam ilmiah gerakan yang dilakukan oleh tubuh manusia disebut dengan fungsi motorik. Proses tumbuh kembang seorang anak selaras dengan kematangan saraf dan otot anak, sehingga sekecil apapun gerakan yang dilakukan oleh seorang anak merupakan hasil interaksi dari berbagai bagian sistem dalam tubuh yang dikendalikan oleh otak, perkembangan motorik merupakan pengendalian gerakan jasmani melalui kegiatan pusat syaraf, urat syaraf dan otot yang terkoordinasi. Perkembangan jasmani anak usia sekolah dasar berupa koordinasi gerakan tubuh seperti berlari, berjinjit, melompat, bergantung, melempar, dan menangkap, serta menjaga keseimbangan. Kegiatan ini diperlukan dalam meningkatkan keterampilan koordinasi gerakan motorik kasar. Tetapi perkembangan motorik pada usia ini menjadi lebih halus dan lebih teratur dibandingkan dengan masa bayinya. mereka terlihat lebih cepat berlari dan pandai meloncat serta mampu menjaga keseimbangan tubuhnya. Untuk memperhalus keterampilan-keterampilan motorik, anak-anak harus terus melakukan aktivitas fisik dan disamping itu anak-anak juga harus dilibatkan dalam aktivitas permainan olahraga senam, berenang, dll. Untuk itu mata pelajaran penjaskes sangat efektif dalam memaksimalkan perkembangan motorik siswa pada usia sekolah dasar. Kata Kunci: Perkembangan Motorik, Siswa Sekolah Dasar, Pelajaran Penjaskes